2018
DOI: 10.1121/1.5055234
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between acoustical and perceptual measures of vocal effort

Abstract: Excessive vocal effort is a common clinical voice symptom, yet the acoustical manifestation of vocal effort and how that is perceived by speakers and listeners has not been fully elucidated. Here, 26 vocally healthy adults increased vocal effort during the production of the utterance /ifi/, followed by self-ratings of effort on a 100 mm visual analog scale. Twenty inexperienced listeners assessed the speakers' vocal effort using the visual sort-and-rate method. Previously proposed acoustical correlates of voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 99 publications
5
35
1
Order By: Relevance
“…Deviant vocal output signatures like hoarseness, is a perceptual feature which is easily detectable in face‐to‐face communication situations and can affect quality‐of‐life, particularly in those individuals using their voices professionally. It is also well known that the objective voice measures used herein have high ecological validity in correlating with perceptual characteristics of abnormal vocal output 74,75 . Therefore, we echo the statement by Van Lierde and colleagues 76 that “…professional voice users and elite vocal performers must be informed before implantation.” In fact, we emphasized the potential for adverse effects on vocal function during the recruitment phase and reiterated this material in our consent process; both in written form and in verbal recapitulation to ensure all participants clearly understood this information before signing the informed consent document and joining the study.…”
Section: Discussionsupporting
confidence: 72%
“…Deviant vocal output signatures like hoarseness, is a perceptual feature which is easily detectable in face‐to‐face communication situations and can affect quality‐of‐life, particularly in those individuals using their voices professionally. It is also well known that the objective voice measures used herein have high ecological validity in correlating with perceptual characteristics of abnormal vocal output 74,75 . Therefore, we echo the statement by Van Lierde and colleagues 76 that “…professional voice users and elite vocal performers must be informed before implantation.” In fact, we emphasized the potential for adverse effects on vocal function during the recruitment phase and reiterated this material in our consent process; both in written form and in verbal recapitulation to ensure all participants clearly understood this information before signing the informed consent document and joining the study.…”
Section: Discussionsupporting
confidence: 72%
“…Increased vocal effort seems associated with a different trend of spectral change. In vocally healthy speakers McKenna and Stepp 84 observed that typical phonation style had the highest L/H ratio (a ratio of low to high spectral energy with cut-off at 4 kHz) and this measure decreased steadily from mild to maximal effort (i.e. decreased spectral slope in vocal effort).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Vocal effort manifests as a series of changes to the voice signal, including those that can be quantified by amplitude-, time-, and spectral-based measures. 22 Effortful voice production is a critical component of voice disorders and is considered to be a component of vocal hyperfunction. 23,24 Therefore, the increased vocal effort that occurs in hyperfunctional voice disorders can be associated with altered patterns of intrinsic and extrinsic laryngeal muscle activation, attempts to compensate for a lack of vocal fold closure, changes in the vibratory patterns of the vocal fold and altered respiratory behavior.…”
Section: Discussionmentioning
confidence: 99%